1988
DOI: 10.1111/j.1502-3885.1988.tb00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Deglaciation pattern indicated by the ice‐margin formations in Northern Karelia, eastern Finland

Abstract: A map has been reconstructed representing the large‐scale glacial and glaciofluvial morphology of Northern Karelia and the adjacent area of Soviet Karelia. Observations have been made on the directions of glacial striae and on the distribution of sub‐aquatic and supra‐aquatic terrain in order to obtain a consistent picture of the course of deglaciation in the area and the factors affecting it. The map indicates that the behaviour of the glacier during the deglaciation was largely governed by the distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Sedimentation in interlobate zones is commonly dominated by glaciofluvial processes, but embraces a complex pattern of sedimentary environments, from subglacial tunnels through ice-walled channels and alluvial fans to subaqueous fans and glacial lakes. Allocation of the aforesaid environments is largely governed by the distribution of subaqueous and supraaqueous areas (Eronen & Vesajoki, 1988). The type of glaciomarginal forms and sedimentation is also related with the type of crevasse system in the marginal part of the ice lobes.…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentation in interlobate zones is commonly dominated by glaciofluvial processes, but embraces a complex pattern of sedimentary environments, from subglacial tunnels through ice-walled channels and alluvial fans to subaqueous fans and glacial lakes. Allocation of the aforesaid environments is largely governed by the distribution of subaqueous and supraaqueous areas (Eronen & Vesajoki, 1988). The type of glaciomarginal forms and sedimentation is also related with the type of crevasse system in the marginal part of the ice lobes.…”
Section: Introductionmentioning
confidence: 99%
“…In their consideration of the course of deglaciation in eastern Finland, Eronen & Vesajoki (1988) conclude that the ice margin retreated from the Salpausselka I marginal formation to the Salpausselka IIposition earlierin the east than furtherwest, whereas the present author has previously put forward the contrary suggestion that the eastern parts of the Salpausselka complexes are in fact younger than the western parts (Forsstrom 1984). Eronen & Vesajoki (1988) base their interpretation on the relatively highlevelsof the glaciofluvialdeltas in the eastern parts of Salpausselka I1 (Figs. 1,2), which are regarded as having been deposited at the stage preceding the formation of the main part of Ss I1 (Saarnisto 1970).…”
mentioning
confidence: 66%
“…However, the major re-advance took place only in the area covered by the Finnish Lake District Ice Lobe but not in the area covered by the Baltic Sea Ice Lobe. Based on glacial landform (eskers) studies in the Ilomantsi area, in the eastern part of Finnish Karelia, Eronen & Vesajoki (1988) also suggested that the so-called Heinola deglaciation took place in the area covered by the Finnish Lake District Ice Lobe. The till stratigraphical results in North Karelia in the northeastern part of the Finnish Lake District Ice Lobe also support the re-advance evidence reported here.…”
Section: Discussionmentioning
confidence: 99%